Karakteristik, Potensi, Keberhasilan Usaha Industri Kain Sasirangan dan Kebijakan Pengembangan Kain Sasirangan sebagai Produk Unggulan Kalimantan Selatan - Anwar, Hj. Khairiyahtul; ., Elrifadah (Universitas Brawijaya, Indonesia, 2012)
This research goal is to describe and examine entrepreneur's characteristics, entrepreneurship potentials and sasirangan industries success in Kalimantan Selatan. Fuiter it also aims to identify andstudy the effort to empower the sasirangan industries enterpreneurs. So this research can give the academic contribution for developing the concept of society welfare through empowering paradigm and contributeto help the regional government to arise unique identity of South Kalimantan. The sample of this research is the enterpreneur of sasirangan industries that has fulfill the standard criteria. Data was taken by spreadingthe questionaires. The variables of enterpreneurs characteristics of sasirangan industries in South Kalimantan have positive and significant effect in success of the effort of sasirangan industries in SouthKalimantan. The variable of SME development policy has proved immoderate both the characteristic of enterpreneurship potential in succesful effort and the effect of entreprenourship potential. This research isconduct to surface that the variable of UKM developing policy will have the significant effect in success ofsasirangan industries in South Kalimantan if it is acted as the independent variable.